In vitro metabolism of 2-ethylhexyldiphenyl phosphate (EHDPHP) by human liver microsomes. Issue 1 (5th January 2015) - Ballesteros-Gómez, Ana; Erratico, Claudio A.; Eede, Nele Van den; Ionas, Alin C.; Leonards, Pim E.G.; Covaci, Adrian
Graphical abstract